The Impact of the Main Determinants and Changes in Agricultural Labour Productivity in Macedonia - Trpeski, Predrag; Cvetanoska, Marijana (European Scientific Journal, ESJ, 2018)
The aim of this paper is to analyze changes and impacts on the level of labour productivity in the agricultural sector in Macedonia in the period from 2006 to 2017. Labour productivity is an important determinant for establishing the competitiveness of a particular sector or overall economy and helps in creating the necessary conditions for economic development. Agricultural sector in many countries represents the basis for growth in gross domestic product. Agriculture plays a key role in development of the national economy in Macedonia as a third largest sector after services and industry. Therefore, in order to increase the agricultural labour productivity, it is necessary to increase agricultural production, i.e., the part of gross domestic product created by the agriculture sector. In this direction, the paper also analyzes the relationship between agricultural labour productivity and gross domestic product and employment in agriculture. Synthesis and analysis, induction and deduction, descriptive statistics, comparative analysis, correlation analysis and regression analysis are used for the purpose of the paper. The results show that changes in gross domestic product in agricultural sector in Macedonia have a greater impact on agricultural labour productivity for the analyzed period compared to the impact of changes in the number of employees in the agriculture sector where the relationship is weak to moderate. Research results also showed that there is a positive and strong quantitative relationship between agricultural labour productivity growth rate and GDP growth rate in Macedonian economy. Agricultural GDP is the determinant which has to be influenced through intensification of agricultural production in order to increase the agricultural productivity.